A Model of Substance Use Tendency Based on Mindfulness with the Mediating Role of Psychological Capital - Mohammadi, Boshra; Belyad, Mohammad Reza; Tari Moradi, Arezoo; Zhian Bagheri, Masoumeh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to examine the relationship between mindfulness and substance use tendency, with the mediating role of psychological capital among senior high school students in Tehran.Methods and Materials: The study employed a descriptive-correlational design using structural equation modeling. The statistical population included all second-cycle high school students in Tehran during spring 2024. A sample of 400 students was selected through multistage cluster sampling. Data were collected using the Substance Use Tendency Questionnaire (Mousavi et al., 1999), the Adolescent and Adult Mindfulness Scale (Dratman et al., 2018), and the Psychological Capital Questionnaire (Luthans et al., 2007). Analysis was conducted using SEM in AMOS-22.Findings: Results showed a significant negative direct effect of mindfulness on substance use tendency (β = −0.28, p < 0.01). Additionally, the indirect effect of mindfulness through psychological capital was also significant and negative (β = −0.12, p < 0.01), resulting in a total effect of β = −0.40. The Sobel test confirmed the mediation effect (Z = 3.21, p < 0.01). Model fit indices indicated an acceptable model fit (CFI = 0.92, RMSEA = 0.059, TLI = 0.90).Conclusion: The findings suggest that mindfulness reduces substance use tendency in adolescents both directly and indirectly by enhancing psychological capital. Enhancing mindfulness and developing psychological capital may serve as effective preventative strategies within educational settings.